[section 1] [evaluating expressions]

(1.)  8 + 3 * 7               here is the problem

=    8 + 21                   multiply

result:  29

(2.) 6 * (3 + 11)              here is the problem

=      84                      multiply

result:   84

(3.)  8 * 7 + 9/9                here is the problem

=     56 + 1                  multiply and divide

result:  57

(4.)  30 - 7*0                    here is the problem

=    30 - 0                    multiply

=   30                       subtract

result:  30

(5.)  (4 + 2)*7               here is the problem

=   42                                multiply

result:  42

(6.)   3[15 - (5 + 3)]              here is the problem

=   3(7)                          subtract

=   21                            multiply

result:  21

(7.)  2[11 * (8/4)]              here is the problem

=    2(11*2)                         divide

=    2(22)                              multiply

=   44                            multiply

result:  44

(8.)   4[(24/6) + 2]               here is the problem

=   4(4 + 2)                          divide

=  24                            multiply

result:  24

(9.)   2[(11*8)/4]                   here is the problem

=    2(88/4)                            multiply

=   2(22)                                 divide

=  44                                    multiply

result: 44

(10.)   8/[(16 - 2)3 + 4]                here is the problem

=   8/[14*3 + 4]                       subtract

=   8/(42 + 4)                       multiply

=    4/23                        reduce

result:  4/23

(11.)  50 + 2x   for x = 20           here is the problem

=   50 + 2(20)                       replace x with 20

=   50 + 40                         multiply

result:  90

(12.)    2p + 2s   for p = 4 and s = 5     here is the problem

=     2(4) + 2(5)                  replace p & s with 4 & 5

=    8 + 10                          multiply

result: 18

(13.)    8/(x - y)  for  x = 10 and y = 6

[here is the problem]

=   8/(10 - 6)           replace x & y with 10 & 6

=  8/4                          subtract

= 2                             divide

result:  2

(14.)  2a + b   for  a = 7 and b = 5         here is the problem

=  2(7) + (5)           replace  a & b with 7 & 5

=  14 + 5                     multiply

result: 19

(15.)  (a + 2b)/5   for a = 10 and b = 2  here is the problem

=  (10 + 2(2))/5       replace a & b with 10 & 2

=    (10 + 4)/5                 multiply

=   2.8                        divide

result:  2.8

(16.) 2(a + b) for a = 4 and b = 5   here is the problem

=   2(4 + 5)           replace a & b with 4 & 5

=  18                        multiply

result:  18

(17.)  10 - 5q  for q = 8         here is the problem

=   10 - 5(8)                   replace q with 8

=  10 - 40                        multiply

=   -30                             subtract

result:  -30

(18.)   10 + 3y  for y = 10           here is the problem

= 10 + 3(10)               replace  y with 10

=  10 + 30                    multiply

result:  40

(19.)   B = 5 + t2  for t = 3              here is the problem

B = 5 + (3)2                 replace t with 3

B = 5 + 9            square the 3